Association of the Systemic Inflammation Response Index with Functional Outcome in Acute Large Vessel Occlusion Stroke Patients Receiving Mechanical Thrombectomy - Wu W; Zhang YP; Qu XG; Zhang ZH (Journal of Inflammation Research)
Wen Wu,1,2 Yu-Pei Zhang,1,2 Xing-Guang Qu,1,2 Zhao-Hui Zhang1,2 1Departments of Critical Care Medicine, Yichang Central People’s Hospital, Yichang, Hubei, 443003, People’s Republic of China; 2The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, 443003, People’s Republic of ChinaCorrespondence: Zhao-Hui Zhang, Department of Critical Care Medicine, Yichang Central People’s Hospital, Yichang, Hubei, 443003, People’s Republic of China, Tel/Fax +86 0717 6481546, Email zhaohuizhang0630@163.comPurpose: The systemic inflammation response index (SIRI) has recently emerged as a novel inflammatory and prognostic marker across various diseases. However, there is limited research examining the relationship between SIRI and 90-day functional outcome in patients with acute large vessel occlusion stroke (ALVOS) undergoing mechanical thrombectomy (MT). This study aimed to investigate the potential of SIRI as an innovative, inflammation-based predictor of 90-day functional outcome.Methods: This retrospective cohort study consecutively recruited 604 Chinese patients with diagnosed ALVOS who underwent MT at the First College of Clinical Medical Science of China Three Gorges University between July 2017 and April 2023. Comprehensive data, including baseline demographic and clinical characteristics, were systematically extracted from electronic medical records. Poor functional outcome at 90 days was defined as modified Rankin Scale (mRS) score ≥ 3. We employed logistic regression models, curve fitting, sensitivity analyses, subgroup analyses, and receiver operating characteristic (ROC) curves to validate the association between SIRI and poor outcome, as well as to assess the predictive efficacy.Results: Final analysis included 604 ALVOS subjects of whom 54.3% experienced poor functional outcome at 90 days. In the multivariate analysis, after adjusting for potential confounders, SIRI remained significantly associated with an elevated risk of poor outcomes (OR 1.18, 95% CI 1.08– 1.28, P < 0.001). Nonlinear curve fitting revealed a reverse J-shaped association between SIRI and poor outcomes, with inflection points at 4.5. Subgroup analyses showed no significant interactions (all P for interaction > 0.05), However, atrial fibrillation demonstrated a significant interaction (all P for interaction = 0.001).Conclusion: SIRI shows promise as a novel prognostic marker for 90-day functional outcome in patients with ALVOS undergoing MT. The identified nonlinear relationship and inflection point may provide valuable insights for risk stratification and clinical decision-making in this specific patient population.Keywords: systemic inflammation response index (SIRI), acute large vessel occlusion stroke (ALVOS), functional outcome, mechanical thrombectomy (MT)